A novel strategy for longevity prolongation of iron-based nanoparticle thin films by applied magnetic force - R. Stefan (2018)
© The Royal Society of Chemistry and the Centre National de la Recherche Scientifique. Zerovalent and other iron-based phases were fabricated in the form of thin films in the presence of a magnetic field. TEM measurements showed the secondary size of nanoparticles to be approximately 15 nm. The crystallinity of the zerovalent nanoparticles was increased by fabrication inside of a magnetic field, which led to increased stability of the nanoparticles in ambient air and to a discovery of a new reaction in which a magnetic field of 0.2 Tesla affected the products of the chemical reaction between iron and nitrogen. Crystallinity and phase change were confirmed by XPS and GIXRD characterization.